Révolution et réflexion comme dialectique éducative chez Gaston Bachelard: une pédagogie du contre et du vers - Martínez Moreno, Arturo (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
In Bachelard, two paths coexist, that of science and that of poetry. It was Georges Canguilhem who recognized that his philosophy practiced a dualism without mutual excommunication of the real and the imaginary. This dualism, born of complementarity, is the foundation of a “pedagogy of no” which aspires to be a “poetic pedagogy”. On the one hand, a visionary and risky epistemology that seeks discursive truth; on the other, a phenomenology that traces poetic images and reverie. It is with this great thinker that science and reason seek a psychoanalysis of objective knowledge and a dialectical approach, where learning oscillates between revolution and reflection, until reaching a new pedagogy where intelligence is truly creative and emancipating. Key words: Bachelard, epistemology, pedagogy of no, imaginary, scientific spirit.